Investigating Factors Influencing Consumer Adoption of Nanofood towards Purchase Intention - Murzidah Ahmad Murad, Mohamad Aidil Hasim, Juhaini Jabar (International Journal of Advanced Science and Technology, 2019)
P3 Sweetener Liquid Drop is one instance of a nanofood product, which can enhance nutritional value, food quality, and taste of product. The main objective of this research is to define the influencing factors affecting consumer adoption of nanofood towards purchase intention, thus determining the most influencing factor affecting on this research. The main sample from 365 of respondents were obtained from the survey carried out in Johor, Malaysia based upon stratified random sampling plan. The model tested in this research elicits 4 influencing factors affecting on consumer adoption, namely: knowledge, trust, perceived benefit and psychological factor. Multi-Regression Analysis (MRA) has shown that trust, perceived benefit and psychological factor have positive significance effects on consumer adoption of nanofood towards purchase intention, while knowledge has insignificant effect on this research. The findings of this analysis can help to enhance consumer understanding towards purchase intention and help to address the gap for future studies